Advanced Nanobiomedical Approaches to Combat Coronavirus Disease of 2019. Issue 3 (18th January 2021) - Lutz, Halle; Popowski, Kristen D.; Dinh, Phuong-Uyen C.; Cheng, Ke
Abstract : New infectious diseases are making themselves known as the human population grows, expands into new regions, and becomes more dense, increasing contact with each other and animal populations. Ease of travel has also increased infectious disease transmission and has now culminated into a global pandemic. The emergence of the novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) in December 2019 has already infected over 83.7 million people and caused over 1.8 million deaths. While there have been vaccine candidates produced and supportive care implemented, the world is impatiently waiting for a commercially approved vaccine and treatment for the coronavirus disease of 2019 (COVID‐19). The different vaccine types investigated for the prevention of COVID‐19 all have great promise but face safety obstacles that must be first addressed. Some vaccine candidates of key interest are whole inactivated viruses, adeno‐associated viruses, virus‐like particles, and lipid nanoparticles. This review examines nanobiomedical techniques for combatting COVID‐19 in terms of vaccines and therapeutics. Abstract : Advancements in nanotechnology offer multiple approaches for producing highly effective vaccines and biocompatible therapeutics to prevent, treat, and ultimately eradicate coronavirus disease of 2019 (COVID‐19). This review examines the benefits of promising vaccine candidates and the challenges each type of vaccine faces and provides an overview of innovative and safe methods for treating COVID‐19.